Effect of herbal plants on quality and microbial safety of milk in eastern Zone of Tigray, Ethiopia - Yemane, H. (International Livestock Research Institute, 2015)
The study was conducted to understand the effect of herbal plants on quality and microbial safety of milk and to identify the best plant used for fumigation of milk container in Eastern zone of Tigray, Ethiopia. A total of 84 respondents, 52.4% (n = 44) from Ganta-afeshum and 47.6% (n = 40) from Kilteawilaelo were interviewed. From these, 81% (n = 68) of them encountered milk spoilage. 70.2% (n = 59) respondents, used herbal plants as fumigators of milk containers to prevent milk spoilage. The milk samples collected from the selected farms were poured in to 6 calabash and 6 plastic containers each with 200 ml of milk. The milk poured in to the untreated plastic and calabash containers were used as control group. Organoleptic tastes like odor and taste as well as physical attributes like temperature and pH were carried out. Standard plate count and coliform count were used for bacterial load determination. Herbal plants namely Olea europaea L, Vernonia amygdalina, Solanum schimperianum hochst, Acacia etbaica schweinf, Aoe elegans were used for milk fumigation. The data obtained were analyzed using SPSS Statistical software version 17.0 (descriptive analysis (frequency), mean comparison T independent test, General leaner model multifactorial repeated two way ANOVA) analysis method were applied. The lowest bacterial count was obtained from milk samples fumigated by V. amygdalina for both standard plate count (7.8x105) and coliform count (4.5x105). The highest bacterial count was recorded from samples of the untreated or control groups. The bacterial count between treated and untreated milk container had statistically significant variation (p = 0.000). Milks samples stored in calabash containers had excellent taste and odor in day one and day two compared to plastic containers. Milk container fumigated with Vernonia amygdalina improve the quality and microbial safety of milk.